Structural and functional annotation of PR/SET Domain (PRDM) protein family: In-silico study elaborating role of PRDM12 mutation in congenital insensitivity to pain. (December 2020) - Mehmood, Sarmad; Dad, Rubina; Ahmad, Arsalan; Ullah, Muhammad Ikram; John, Peter; Ali, Amjad; Hubner, Christian A.; Mohyuddin, Aisha; Hassan, Muhammad Jawad
Highlights: Whole Exome Sequencing identified reported mutation in PRDM12 gene in a patient with insensitivity to pain. All 19 PRDM domain containing proteins were structurally analyzed. Some of them cause neurological disorders in human including PRDM12. PRDM12 was further studied through in silico approaches. Abstract: Congenital insensitivity to pain (CIP), classified as a type of hereditary sensory and autonomic neuropathies, is a rare disease in which the affected individuals fail to perceive sensation of pain. One of the PR/SET Domain Proteins, PRDM12, has been identified in recent past as a candidate gene for congenital insensitivity to pain. In the present study, we performed whole exome sequencing in a Pakistani family with CIP phenotype to ascertain the causative mutation. We identified a previously described alanine repeat duplication in PRDM12 (Ala353_Ala359dup) in this family. After this, we performed structural annotations for PR/SET Domain (PRDM) containing protein family to prognosticate the potential hypothetical structure of PRDM proteins with physical and chemical parameters. Out of nineteen members of this family, four members (PRDM5, PRDM8, PRDM12 and PRDM13) were specially focused because of their role in neurological disorders. Predictions about structure and interactions of these proteins revealed novel interacting molecules and pathways. Detailed in silico analysis of PRDM12 was performed to elaborate importance of its domain structure in interaction with other proteins and its role in pain insensitivity phenotype. These results have substantially enhanced our understanding regarding the etiology of congenital pain insensitivity and would stimulate further research on therapy and prevention.